Pengawasan Mutu pada Pengolahan Dodol Salak di CV Duta Gunung Salak - NINGSIH, NI KADEK AYU; SUAMBA, I KETUT; SARJANA, I DEWA GEDE RAKA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2016)
Abstract The Quality Control of Dodol Salak Processing at CV Duta Gunung Salak CV Duta Gunung Salak has implemented a quality control since 2005. In fact, there is damage sallaca paste 2014 with the percentage of damage reaches 14.78%. The purpose of this study is to investigate the implementation and the quality control system of processing sallaca paste approach control map and the cost of quality. The primary data comes from six respondents from the company. Secondary data were obtained from the literature and documents of the company. Analysis of data derived from descriptive analysis, qualitative, map control, and quality costs. The results showed that the implementation of quality control to meet the standard corporate or BPOM views of good manufacturing practices. The damage occurred in the processing and marketing as much as 14.78% of the total production. Quality control using quality cost that the company has not done well, the real total quality control issued by the company Rp 17,616,655 is greater compared to total quality control of the optimum amount of Rp 14,366,692. Suggested, companies need to be handling the marketing process.
Keywords: processing; quality control; statistical quality control